Fabrication of aluminum matrix composites reinforced with Al2ZrO5 nano particulates synthesized by sol-gel auto-combustion method - Shameli, Kamyar; Ahmad @ Ayob, Mansor; Khorramie, Saeid Abedini; Baghchesara, Mohammad Amin; Lotfi, Roshanak; Shabanzadeh, Parvaneh (National Institute of Materials Physics, National Institute of Optoelectronics, 2013)
Nanocrystalline Al2ZrO5 with particle size of about 38 nm was directly synthesized by combination of sol−gel auto-combustion and ultrasonic irradiation techniques from metal nitrates and glycine as precursors. The overall process involves formation of homogeneous sol, formation of dried gel and combustion process of the dried gel. Aluminum alloy matrix composites reinforced with 0.75%, 1.5% and 2.5% Al2ZrO5 nanoparticles were fabricated via stir casting method and the fabrication was performed at various casting temperatures. The resulting composites were tested for their nanostructure and present phases by SEM and XRD analysis. Optimum amount of reinforcement and casting temperature were determined by evaluating the density, hardness and compression strength of the composites. Al matrix alloy reinforced by Al2ZrO5 nanoparticles improves the hardness and compressive strength of the alloy to maximum values of BHN 61 and 900 MPa, respectively. The most improved mechanical properties are obtained with the specimen including 1.5% Al2ZrO5 produced at 850 °C.